PENERAPAN TOTAL QUALITY CONTROL (TQC): PENGARUH QUALITY CONTROL CIRCLE (QCC), PLAN-DO-CHECK-ACTION (PDCA) DAN KESADARAN AKAN MUTU TERHADAP MOTIVASI KERJA KARYAWAN (Studi Empiris pada Perusahaan Manufaktur dan Jasa di Gresik) - Erlina Diamastuti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2004)
The purpose of the study is to find out the application of total quality control on manufactur and services industries in Gresik by finding out on how the influence of quality control circle (GCC). Plan-do-Check-Action and the quality awareness as the dimension of total quality control toward the employee 's work motivation. The researcher has .formulated the hipotesis of this study that are Quality Conlrol Circle (QCC). Plan-Do-Check-Action and the quality awareness have influence toward the employee's work motivation. The quality control circle has sign!ficance influence among those third variables. From the result of the analysis shows that quality control circle (QCC), quality awareness and Plan-Do-Check-Action have significance influences toward the employee's work motivation. This conclusion relied on the calculation showing the value of ratio F of 19,552 ·· F table - 1,53. Based on I-test might be concluded that quality control circle has significance influence toward work motivation, while the quality awareness and Plan-Do-Check-Action doesn't have significance influence toward the employee's work motivation